A Clinical Study of Medulloblastoma in Correlation with Molecular Biology and Histological Variations in Childhood Medulloblastoma in Northeast India - Bhuyan, Mrinal; Haloi, Hriday; Baishya, Basanta Kumar; Haque, Inamul (Indian Journal of Neurosurgery, 2019)
Introduction Medulloblastoma is a common embryonal childhood tumor predominantly seen in children (1-3). Medulloblastoma can be classified in different histological and molecular subgroups, each of them characterized by discrete clinical presentation, demographic features, prognosis, and outcome. This may help in patient stratification, treatment strategy, design, and implementation of the targeted therapy.Aims and Objectives We aimed to study the patients included in the study with regard to variables such as age, sex, clinical features, and various modes of management in our hospital. We also studied histological and molecular variations in the group.Materials and Methods A prospective study was carried out in the Department of Neurosurgery, Gauhati Medical College and Hospital, Guwahati, from January 2016 to August 2017. Sixty-five patients diagnosed as medulloblastoma were included in the study. We studied the spectrum of clinical findings, radiological and pathologic characteristics, modes of surgical management, and postoperative complications. Study of molecular biology was done in the Department of Bioengineering, Gauhati University.Results and Observation Results and observations were obtained based on the age and radiological, pathological, histological, and molecular variants.Conclusion Medulloblastoma is seen more in pediatric age group and males. Classical variant was the most common type with mostly vermian location followed by desmoplastic variant which was paravermian to lateral in location. Postoperatively, radiotherapy and chemotherapy have proved very useful. Statistical analysis suggested a significant correlation between age groups and complications and also between histological types and associated complications. P53 mutation was noted in a section of the study population but majority cases did not show mutations in selected genes.
Keywords: medulloblastoma; histopathology; genetics